Analisis Hubungan Sosial Ekonomi dan Jenis Kelamin dengan Stunting pada Balita di Sangiangtanjung, Lebak Banten - Terry Y.R. Pristya; Azizah Muliha Fitri; Widayani Wahyuningtyas (STIKes Hang Tuah Pekanbaru, 2020)
Stunting is an indicator of nutritional status problems. Some of the risk factors that cause stunting are very complex. This study aimed to analyze the relationship between socioeconomic and sex with stunting in children under five. This research was a combination of quantitative and qualitative research methods. Quantitative data were obtained from secondary data from the Nutrition Status Monitoring (PSG) Sangiangtanjung 2019. The sample was 507 children under five of age in Sangiangtanjung Village who met the inclusion and exclusion criteria. The variables analyzed included stunting, socio-economic, and sex was analyzed using the Fisher exact test and chi-square. Qualitative data were obtained from in-depth interviews with a village official and a village midwife. The results showed that the prevalence of stunting in Sangiangtanjung Village was 2.8%. All variables showed no relationship with stunting, consist of: socioeconomic (p-value = 0.845) and gender (p-value = 0.604). The results of interviews obtained in-depth information about the risk factors for stunting, the low socio-economic level of the community, the reluctance of pregnant women to antenatal care in the first trimester, and the belief in some stigma regarding restrictions on the consumption of certain foods that are good for health. All of these factors were included in the fundamental factors. There was a need for handling efforts at the downstream level by increasing the knowledge of pregnant women about risk factors for stunting and their prevention through pregnant women classes.